PENGARUH KOMUNIKASI PEMASARAN TERHADAP PENINGKATAN JUMLAH NASABAH ASURANSI BUMI ASIH JAYA MEDAN - Ardial Ira Yustina (Universitas Medan Area, 2012)
This research is conducted to know how execution of marketing communications by employees of Glorious Earth Asih Insurance. The issues of this research is: